DISTRIBUTED ARCHITECTURE OF UAV CONTROL AND NAVIGATION SYSTEM - SVYSTUN, SERHIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The rapid development of unmanned aerial vehicle (UAV) technology has underscored the necessity for sophisticated control and navigation systems capable of managing the complexities of modern aerial operations. This manuscript presents a novel distributed architecture for UAV control and navigation that significantly enhances cooperative tasks and operational efficiency in dynamic environments. Our architecture addresses the challenges inherent in traditional centralized systems, particularly scalability and resilience to failures. The core of our proposed architecture is built on a decentralized approach where each UAV functions as an autonomous agent equipped with its own sensing, processing, and communication capabilities. This allows for a distributed decision-making process, where UAVs share information and collaboratively formulate strategies without relying on a central command. Such a configuration not only reduces the communication load but also mitigates the single point of failure risk, enhancing system robustness. We introduce a two-layer control scheme in the architecture. The first layer involves local control loops on individual UAVs that handle real-time navigation and obstacle avoidance. The second layer, supervisory control, coordinates among the UAVs to ensure mission objectives are met efficiently. This hierarchical setup enables UAVs to react swiftly to local environmental changes while aligning their actions towards common goals. Simulation results demonstrate the effectiveness of our distributed architecture in various scenarios. These include navigating challenging terrains, coordinating large fleets of UAVs, and managing tasks that require high levels of autonomy and cooperation. We also show that our system can dynamically adjust to unexpected changes in the environment, such as sudden weather shifts or communication disruptions.
Keywords: distributed architecture; unmanned aerial vehicles; control systems; navigation systems; cooperative search